2016
DOI: 10.1093/nar/gkw1083
|View full text |Cite
|
Sign up to set email alerts
|

OUP accepted manuscript

Abstract: Fusion gene is an important class of therapeutic targets and prognostic markers in cancer. ChimerDB is a comprehensive database of fusion genes encompassing analysis of deep sequencing data and manual curations. In this update, the database coverage was enhanced considerably by adding two new modules of The Cancer Genome Atlas (TCGA) RNA-Seq analysis and PubMed abstract mining. ChimerDB 3.0 is composed of three modules of ChimerKB, ChimerPub and ChimerSeq. ChimerKB represents a knowledgebase including 1066 fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The difference in percentages of fusions supported by a DNA level alteration likely reflected the sensitivity differences between SNP arrays and DNA sequencing. For benchmarking purposes, we curated a list of 321 known fusions ( Supplementary Table S1 ) by integrating Mitelman ( 13 ), ChimerPub ( 11 ) and Cosmic fusions ( 14 ). We applied the same validation strategies to this list and observed validation rates of 68 and 52%, respectively, for sequencing-based and array-based approaches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in percentages of fusions supported by a DNA level alteration likely reflected the sensitivity differences between SNP arrays and DNA sequencing. For benchmarking purposes, we curated a list of 321 known fusions ( Supplementary Table S1 ) by integrating Mitelman ( 13 ), ChimerPub ( 11 ) and Cosmic fusions ( 14 ). We applied the same validation strategies to this list and observed validation rates of 68 and 52%, respectively, for sequencing-based and array-based approaches.…”
Section: Resultsmentioning
confidence: 99%
“…All fusion candidates were subject to six additional filters ( Supplementary Methods ). We integrated three resources including Mitelman ( 13 ), ChimerPub ( 11 ) and Cosmic fusions ( 14 ) to build a positive control fusion list (the white list). Each fusion on the list had support from at least three independent publications, leading to a list of 321 unique gene–gene fusions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 001 and 7992 fusion transcript candidates and their related information were downloaded from the ChimerDB 3.0 ( http://ercsb.ewha.ac.kr/fusiongene , December 2016) ( 16 ) and TCGA fusion Data Portal ( http://54.84.12.177/PanCanFusV2/ , December 2014) ( 17 ), respectively. For the ChimerDB fusion transcripts, we found that 13 729 were derived from TCGA samples.…”
Section: Data Integration and Annotationsmentioning
confidence: 99%
“…In the past, numerous resources have been developed to maintain a wide range of information related to instabilities in genome and chromosomes such as i) TICdb, which contain information about chromosomal translocation breakpoint in human tumors [20], ii) HYBRIDdb, maintains information of hybrid genes in humans [21], iii) dbCRID, contains information about chromosomal rearrangement in diseases [22], iv) chimerDB3.0 is a resource of fusion genes [23] and v) COSMIC is a Catalogue of Somatic Mutations in Cancer [24]. Since the discovery of CFSs, several lines of evidence suggest their involvement in human disease progression, as CFSs are preferred sites for exogenous DNA insertion, chromosomal translocation, re-arrangement, and breakpoint.…”
Section: Introductionmentioning
confidence: 99%